Pengaruh Karakteristik Individu,Karakteristik Pekerjaan, Dan Karakteristik Organisasi Terhadap Kinerja Pegawai Kontrak (Studi Pada FISIP ULM Banjarmasin) - Fathur Rahman; Emy Rahmawati; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2020)
The purpose of this study was 1) to analyze the partial effect of individual characteristics on the performance of the employees of the FISIP ULM Banjarmasin contract, 2) to analyze partially significant influence of job characteristics variables on the performance of the employees of the Banjarmasin ULM FISIP contract, 3) analyze partially significant influence of organizational characteristics on performance employee of the ULM FISIP contract contract, 4) analyzing the simultaneous significant influence of individual characteristics, job characteristics and organizational characteristics on the performance of the Banjarmasin FISIP ULM contract employees.The type of research used is causal research. The population in this study were employees of the FISIP ULM Banjarmasin contract with a sample of 38 people and sampling techniques using saturated sampling techniques. Data analysis method uses multiple linear regression analysis.The results showed that 1) there was no partially significant effect of individual characteristics on the performance of Banjarmasin ULM FISIP contract employees, the effect of which was -23.9%, 2) there was a partial significant influence on job characteristics on the performance of the FISIP ULM Banjarmasin contractor, the effect that is 38.9%, 3) there is a partial significant effect of organizational characteristics on the performance of employees of the Banjarmasin ULM FISIP contract and has the most dominant influence on the variables of individual characteristics and job characteristics, the effect of which is 41.8%, 4) there is a significant influence Partial individual characteristics, job characteristics and organizational characteristics of employee performance of the FISIP ULM Banjarmasin contract, with simultaneous influence of 33.6%.Keywords: Individual Characteristics, Job Characteristics, Organizational Characteristics, Contract Employee Performance